Brand Jamaica : reimagining a national image and identity - Johnson, Hume N.; Gentles-Peart, Kamille (University of Nebraska Press, 2019)
"Brand Jamaica is an empirical look at the postindependence national image and branding project of Jamaica within the context of nation-branding practices at large. Although a tiny Caribbean island inhabited by only 2.8 million people, Jamaica commands a remarkably large presence on the world stage. Formerly a colony of Britain and shaped by centuries of slavery, violence, and plunder, today Jamaica owes its popular global standing to a massively successful troika of brands: music, sports, and destination tourism. At the same time, extensive media attention focused on its internal political civil war, mushrooming violent crime, inflation, unemployment, poverty, and abuse of human rights have led to perceptions of the country as unsafe. Brand Jamaica explores the current practices of branding Jamaica, particularly within the context of postcoloniality, reconciles the lived realities of Jamaicans with the contemporary image of Jamaica projected to the world, and deconstructs the current tourism model of sun, sand, and sea. Hume Johnson and Kamille Gentles-Peart bring together multidisciplinary perspectives that interrogate various aspects of Jamaican national identity and the dominant paradigm by which it has been shaped. "--